2013
DOI: 10.1093/toxsci/kft213
|View full text |Cite
|
Sign up to set email alerts
|

An F1-Extended One-Generation Reproductive Toxicity Study in Crl:CD(SD) Rats With 2,4-Dichlorophenoxyacetic Acid

Abstract: 2,4-Dichlorophenoxyacetic acid (2,4-D) was assessed for systemic toxicity, reproductive toxicity, developmental neurotoxicity (DNT), developmental immunotoxicity (DIT), and endocrine toxicity. CD rats (27/sex/dose) were exposed to 0, 100, 300, 600 (female), or 800 (male) ppm 2,4-D in diet. Nonlinear toxicokinetic behavior was shown at high doses; the renal clearance saturation threshold for 2,4-D was exceeded markedly in females and slightly exceeded in males. Exposure was 4 weeks premating, 7 weeks postmating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 75 publications
1
30
1
Order By: Relevance
“…There were no effects in the Marty et al (2010) EOGRT study (published in Marty et al 2013) considered to reflect an androgenic or anti-androgenic mode of action. Although there were several study findings that could support potential anti-androgenicity, these were found either not exposurerelated, not replicated across generations, or were attributable to other factors such as randomization artifacts.…”
Section: Mammalian Studiesmentioning
confidence: 88%
See 4 more Smart Citations
“…There were no effects in the Marty et al (2010) EOGRT study (published in Marty et al 2013) considered to reflect an androgenic or anti-androgenic mode of action. Although there were several study findings that could support potential anti-androgenicity, these were found either not exposurerelated, not replicated across generations, or were attributable to other factors such as randomization artifacts.…”
Section: Mammalian Studiesmentioning
confidence: 88%
“…The single exception to the guidelines for these assays was that it was considered appropriate to limit the high concentration in the first four EDSP in vitro assays to 100 lM, rather than the guideline-recommended 1 mM, because the 100 lM concentration was equivalent to serum concentrations at or slightly above the TSRC (slightly above the inflection point for non-linear TK) in rats dosed with 2,4-D in the diet in the EOGRT study (Marty et al 2010;Marty et al 2013;Saghir et al 2013). As noted previously, responses seen only in the non-linear TK range are not regarded as relevant to human risk assessment.…”
Section: Edsp Tier I In Vitro Studiesmentioning
confidence: 99%
See 3 more Smart Citations